THE IMPACT OF ORGANIZATIONAL AND TECHNOLOGICAL FEATURES OF WAREHOUSE FACILITIES ON THE LEVEL OF AUDIT RISK IN THE AUDIT OF THE MATERIAL EXPENSES OF THE ENTERPRISES ON THE PRODUCTION OF REINFORCED CONCRETE STRUCTURES - Селіщев, C. В. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2014)
The main risks of distortion of the accounting data about the expenses of enterprises for the production of concrete structures associated with organizational and technological features of the warehousing are determined in the article. The peculiarities of storage of the basic kinds of materials and the correspondent audit risks associated with them are considered.